Improving Project Time Estimation in Game Development: Rayleigh Distribution and Program Evaluation and Review Technique Approach - Ghiffari, Mochamad Haikal; Budi Mulyono , Nur (Jurnal sosial dan sains, 2025)
The video game industry has grown exponentially over the past few decades, becoming a dominant force in the global entertainment sector. Despite its rapid growth, the game development process remains highly complex and distinct from traditional software development, requiring a creative and agile approach. This paper addresses the challenge of inaccurate time estimation in game development projects, which often results from the inherent uncertainty inherent in the iterative and creative nature of the industry. This study integrates the Critical Path Method (CPM) and the Program Evaluation and Review Technique (PERT) with the Rayleigh distribution to improve the accuracy of time estimation in the context of high uncertainty. Data from a completed game development project by an Indonesian game company is analyzed using this methodology. The results show that the Rayleigh-PERT model, with 70% confidence and an expert quality estimate of 0,3, provides the most accurate time estimation, showing only a 4,26% deviation from actual project performance, compared to 20% for CPM and 15,2% for traditional PERT. This research contributes to improving project management in the video game industry by incorporating uncertainty into time estimation, offering more realistic schedules for game development projects, and improving overall project execution.